2016
DOI: 10.4236/msa.2016.711055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nevirapine Release Kinetics from Polycaprolactone Hybrids

Abstract: The Nevirapine (NVP)/Polycaprolactone (PCL)/Nanoparticles hybrids systems have been developed as a potential platform for drug delivery, by solvent cast, as thin films. NVP, an antiretroviral drug, was included within PCL matrix containing three types of nanoparticles: an organoclay layered silicate Viscogel S7® (3% w/w), hydrophilic silica oxide particles Aerosil® A20 (0.25% w/w) and titanium dioxide particles (0.25% w/w). These systems were characterized by X-ray diffraction (XRD), Fourier-transform infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The spinlattice relaxation parameters involve changes in thermal equilibrium of spin systems and the responses are intrinsically related to the system´s molecular dynamics, which is derived from the morphology of the system (Silva et al 2016). This way, the relaxation parameters are of great value to understand the drug dispersion in the polymer matrix, the interaction between drug and polymer, the molecular dynamics of drug-polymer and the molecular domains formation in an organic material (Monteiro et al 2016).…”
Section: Time-domain Nuclear Magnetic Resonancementioning
confidence: 99%
“…The spinlattice relaxation parameters involve changes in thermal equilibrium of spin systems and the responses are intrinsically related to the system´s molecular dynamics, which is derived from the morphology of the system (Silva et al 2016). This way, the relaxation parameters are of great value to understand the drug dispersion in the polymer matrix, the interaction between drug and polymer, the molecular dynamics of drug-polymer and the molecular domains formation in an organic material (Monteiro et al 2016).…”
Section: Time-domain Nuclear Magnetic Resonancementioning
confidence: 99%
“…Monteiro et al showed that the crystallization of the PCL was affected with the introduction of nanoparticles and a specific drug, modifying its semicrystalline structure of the PCL and reducing its crystallinity [ 59 ]. After the addition of βCP–NP, there was a decrease in full width at half maximum (FWHM) the peak of the plane (110), corresponding to a narrowing of the peak by 21.4°.…”
Section: Resultsmentioning
confidence: 99%
“…Polycaprolactone (PCL) is one of the most widely employed FDA approved biodegradable and biocompatible polymer, which is non-toxic and has a great permeability to several drugs. [16] In this study, PCL forms the polymeric core for the encapsulation of drug molecules in hybrid NPs.…”
Section: Nateglinidementioning
confidence: 99%